2018
DOI: 10.3390/ma12010007
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Phase Model Characterizing the Low-Velocity Impact Response of SMA-Reinforced Composites under a Vibrating Boundary Condition

Abstract: Structural vibration induced by dynamic load or natural vibration is a non-negligible factor in failure analysis. Based on a vibrating boundary condition, the impact resistance of shape memory alloy (SMA)-reinforced composites was investigated. In this investigation, a modified Hashin’s failure criterion, Brinson’s model, and a visco-hyperelastic model were implemented into a numerical model to characterize the mechanical behavior of glass fiber/epoxy resin laminates, SMAs, and interphase, respectively. First,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The effect of embedding SMA wires into laminated CFRP and GFRP beams on the impact behavior was studied. M. Chang et al [66] Modified Hashin failure criterion, Brinson model, and a visco-hyperelastic model.…”
Section: Cfrp and Gfrpmentioning
confidence: 99%
“…The effect of embedding SMA wires into laminated CFRP and GFRP beams on the impact behavior was studied. M. Chang et al [66] Modified Hashin failure criterion, Brinson model, and a visco-hyperelastic model.…”
Section: Cfrp and Gfrpmentioning
confidence: 99%
“…The aim is to manufacture SMA-based composite panels for the reduction of the sonic fatigue in aeronautic structures. Moreover, in [ 69 , 70 , 71 , 72 , 73 ] the superior performance in terms of energy absorption and impact response of Shape Memory Alloy Hybrid Composites (SMAHC) is assessed. Other applications of SMA can be related to SMA wires embedded in complex wing structures [ 74 , 75 , 76 ], while in [ 77 ], SMA wires interact with a supportive system of pins and springs to actuate an articulated control surface.…”
Section: Overview Of the State Of The Art Of Sma Actuatorsmentioning
confidence: 99%
“…Guida et al [ 8 ] studied the impact dynamics of an SMA‐carbon fiber hybrid composite and found that SMA fibers considerably increased energy absorbing capacity of the composite. Similarly, Chang et al [ 9 ] concluded that embedding SMA wires into composite laminates can improve the impact resistance and reported an increase from 15% to 30% in absorbed energy. Dahnke et al [ 10 ] studied the influence of SMA addition into composites and observed an increase of the energy absorption capacity of the composite due to the high ductility of the SMA wires.…”
Section: Introductionmentioning
confidence: 97%
“…[1][2][3][4] A number of studies have shown that the use of SMA fibers in polymer composites can improve damping properties, impact resistance, and ductility of the composites. [5][6][7][8][9][10][11] Katsiropoulos et al [7] investigated the effect of superelastic SMAs in improving the damping behavior of polymer composites and observed that the incorporation of SMA wires can significantly improve the damping characteristics. Guida et al [8] studied the impact dynamics of an SMAcarbon fiber hybrid composite and found that SMA fibers considerably increased energy absorbing capacity of the composite.…”
Section: Introductionmentioning
confidence: 99%